2016
DOI: 10.21037/jtd.2016.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Association between postoperative bulla neogenesis at the staple line and resected lung weight for primary spontaneous pneumothorax: a retrospective study using the inverse-probability of treatment weighted method in patients grouped according to age

Abstract: and O group (≥25 years, 40 sites). We used the inverse-probability of treatment weighted (IPTW) method to adjust for the heterogeneity in their backgrounds. POBN was diagnosed by computed tomography. Results: Cox regression analysis for the O group indicated that LW ≥3.0 g was a significant risk factor for POBN (P=0.049). For the Y group, no association between lung weight and POBN was observed. Conclusions: A LW ≥3.0 g is a significant risk factor for POBN in individuals aged ≥25 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Recently, numerous etiologies of recurrent pneumothorax following VATS have been proposed. While missed bullae have been recognized as the reason for recurrent pneumothorax following VATS, new bullae formation is now being considered an important etiology (4)(5)(6)(7). We have previously reported that higher tension in the staple line which was associated with bulky resection during VATS, increased the risk of recurrence (7).…”
Section: Original Articlementioning
confidence: 99%
“…Recently, numerous etiologies of recurrent pneumothorax following VATS have been proposed. While missed bullae have been recognized as the reason for recurrent pneumothorax following VATS, new bullae formation is now being considered an important etiology (4)(5)(6)(7). We have previously reported that higher tension in the staple line which was associated with bulky resection during VATS, increased the risk of recurrence (7).…”
Section: Original Articlementioning
confidence: 99%
“…Tsuboshima et al (5,6) hypothesized that a greater extent of lung resection theoretically increased the tension applied to the staple line on the residual lung and that a longer staple line of the residual lung had the more opportunities to cause postoperative bulla neogenesis. Their results showed that a lung weight of ≥1.5 g was a significant risk factor for postoperative bulla neogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mechanical stretch may develop on the boundary line. The hypothesis that mechanical stretch due to lung wedge resection may affect postoperative bulla neogenesis was reported [14,15]. As a result, it is possible that postoperative bulla neogenesis or tear may develop due to postoperative recurrence.…”
Section: Commentmentioning
confidence: 99%
“…This was a retrospective study, and patient backgrounds were heterogeneous. Therefore, we evaluated the feasibility of GPC using propensity score to adjust for the heterogeneity in their backgrounds because this method has previously been used to adjust for these factors in retrospective studies [15][16][17]. In addition, to consider the follow-up time, we used the Kaplan-Meier method and Cox regression analysis but not the c 2 test to evaluate the postoperative recurrence rates.…”
Section: Commentmentioning
confidence: 99%